Forage yield, soil fertility and carbon dynamics of calliandra (Calliandra calothyrsus meissn,) in coconut plantation - Jilna Joy (Departament of Silviculture and Agroforestry , College of Forestry, 2017)
A study entitled “Performance of calliandra (Calliandra calothyrsus Meissn.) under diverse management regimes in a coconut based hedge row fodder production system” was carried out at Instructional Farm, College of Horticulture, Vellanikkara during 2014-2015. The main objective of the study was to assess the influence of management practices like tree density, pruning height and pruning frequency on initial growth, forage yield and nutritional qualities of calliandra intercropped in coconut gardens under humid tropical conditions of Kerala. The treatments consisted of three levels of plant density (27,777; 22,222 and 17,777 plants ha-1), three levels of pruning frequency (8, 12 and 16 weeks interval) and two levels of pruning height (0.5m and 1m) in all possible combinations laid out under factorial randomized block design with three replications. The results revealed that various management practices had a profound influence on the forage yield and quality aspects of calliandra when grown as an intercrop in coconut garden. Comparing plant densities, highest density stand (27,777 plants ha-1) yielded 55 percent more forage (11.73Mg ha-1yr-1, dry basis) than the lowest density (17,777 plants ha-1), with higher foliage fraction. Quality parameters of forage like crude protein, ash, dry matter, phosphorus and potassium content increased and crude fibre content decreased at higher densities indicating closer spacing for production of tender nutritive fodder. Pruning at the prolonged interval of 16 weeks yielded more total forage, but the majority of the fodder comprised of stem fraction as indicated by the poor leaf-stem ratio. Leaf –stem ratio of fodder harvested at 8 and 12 weeks showed an increment of 125 percent over that of the 16 weeks interval, indicating more foliage production than stem fractions when harvested at shorter intervals. Pruning frequencies also had profound influence on nutritive value of the forage. Harvesting at shortest interval of 8 weeks and 12 weeks yielded fodder with maximum crude protein, phosphorus and potassium content when compared to 16 weeks. Ash and dry matter content in 99 fodder was significantly higher at the longest interval of 16 weeks. Crude fibre content of forage increased sharply from 28.33 to 49.98 percent by prolonging the harvest interval from 8 to 16 weeks thereby adversely affecting the palatability of the forage. Pruning height showed more prominent influence on forage yield of calliandra than the nutritive parameters. Dry fodder yield increased from 8.11 to 10.81 Mg ha-1yr-1 with increasing pruning height from 0.5 to 1m, with a higher leaf-stem ratio for taller stocks. Similarly there was a significant improvement in CP yield from taller stocks (1.67 Mgha-1 )when compared to shorter ones (1.23 Mgha-1) The interaction effects of plant density, pruning height and pruning frequency had no significant effect on yield and quality parameters of callianrda. The highest yielding combination (13.39 Mg ha-1dry basis) was found to be D1H2F2 (27,777 plants ha-1 + pruning height 1 m + pruning interval 12 weeks ) with higher foliage fraction and better nutritive parameters, compared to all other management levels, which were inferior either in forage yield or nutritive value or palatability of forage. On the whole, the study revealed that forage yield and quality of young stands of calliandra underneath coconut garden could be optimized at the cheapest level by adopting a tree density of 27,777plants ha-1, pruning height of 1m and pruning interval of 12 weeks. Moreover, based on the growth and yield performance and quality aspects, it is found that calliandra is a promising fodder tree, which can be successfully integrated with the existing coconut gardens of Kerala. Establishment and proper management of calliandra in coconut garden at appropriate management levels thus offers a cheap source of quality forage to Kerala farmers against the highly expensive concentrate feeds.